Recently published articles by faculty members (VITAL, 2025)
UAN School of Medicine professors have recently published articles on anxiety and associated factors, human identification by isotopic variation, emotional recognition in anxiety disorders, pediatric tissue engineering and genetic studies in cell lines.
Keywords: Anxiety; Human identification; Tissue engineering; Emotional recognition; Genetics